Evaluation of behavioural and neurochemical effects of psilocybin in mice subjected to chronic unpredictable mild stress - Ines Erkizia-Santamaría; Igor Horrillo; Nerea Martínez-Álvarez; Daniel Pérez-Martínez; Guadalupe Rivero; Amaia M. Erdozain; J. Javier Meana; Jorge E. Ortega (Translational Psychiatry)
Abstract Depression and anxiety are disabling and high incidence mental disorders characterized by phenotypic heterogeneity. Currently available treatments show severe limitations. Thus, there is an urgent need for effective treatments in this population. In the search for novel rapid-acting antidepressants, the psychedelic psilocybin has emerged as a promising therapy in several clinical trials. However, its antidepressant mechanism of action is still not well understood. The aim of the present study was to evaluate the therapeutic potential of psilocybin in ameliorating the adverse behavioural and neurochemical consequences of chronic stress. To this end, a chronic unpredictable mild stress (CUMS) animal model was used, and psilocybin treatment was administered (two doses of 1 mg/kg, i.p., administered 7 days apart). Psilocybin reversed impairments in anhedonia and behavioural despair dimensions of depressive phenotype but not in apathy-related behaviour. Psilocybin administration was also able to exert an anxiolytic-like effect on treated animals. Physiological alterations caused by stress, indicative of a hyperactive hypothalamic-pituitary-adrenal axis (HPA), were not reversed by psilocybin. When neuroplasticity-related proteins were assessed in cerebral cortex, brain-derived neurotrophic factor (BDNF) was found to be decreased in stressed animals, and treatment did not reverse such impairment. Psilocybin administration increased the expression and function of serotonin-2A-receptor (5HT2AR) in brain cortex of control and CUMS groups. Furthermore, psilocybin treatment caused a selective increase in the expression of glucocorticoid-receptor (GR) in brain cortex of CUMS mice. In conclusion, psilocybin was able to rescue impairments in the depressive phenotype, and to induce anxiolytic-like effects. Furthermore, an enhancement in sensitivity to psilocybin-induced HTR was observed following a booster dose. Altogether, this work provides new knowledge on the putative benefit/risk actions of psilocybin and contributes to the understanding of the therapeutic mechanism of action of psychedelics.